Successful Treatment of Severe Adenoviral ARDS Using Cidofovir in a Case with Cerebral Palsy - Emrah Gün; Tanıl Kendirli; Merve Havan; Serhan Özcan; Serdar Balsak; Edin Botan; Hatice Kübra Konca; Erdal İnce (Journal of Pediatric Emergency and Intensive Care Medicine, 2021)

(untitled)
Adenovirus is a non-enveloped, double-stranded DNA virus that can cause infections in the upper and lower respiratory tract, conjunctiva, and gastrointestinal tract. Adenovirus infections are usually mild but may cause mortality and morbidity, especially in immunocompromised patients. Cidofovir may be used to treat adenovirus. Cidofovir is an antiviral with a virostatic effect, especially effective for adenovirus and herpes virus. In this case report, we present a 15-year-old patient with adenovirus-induced severe acute respiratory distress syndrome, who was referred to us for renal failure and successfully treated with cidofovir.